Model Penganggaran Terpadu Berbasis Priority Quality: Studi Sekolah Dasar Integral Lukman Hakim Jember: Integrated Budgeting Model Based on Priority Quality: A Case Study of Lukman Hakim Integral Elementary School, Jember - Zainuddin Al Haj Zaini (Fenomena, 2018)
The low quality of education in Indonesia is largely attributed to ineffective financial management in educational institutions, particularly at the elementary school level. This study aims to analyze and discover the principles, processes, and strategies of educational financing management to improve school quality. A qualitative approach with a multi-case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal three main components. First, the financing management principles are developed based on religious values, shared funding responsibility, competitive Islamic education quality, compliance with national and international standards, and trustworthy financial management. Second, the management process includes priority-based integrated budgeting planning, implementation through a grade-based system, internal evaluation models, and financial and performance audits for accountability. Third, the strategies involve budgeting through RKAS/RKAM, accounting managed by the foundation treasurer, and auditing conducted by foundation leaders and stakeholders. The study concludes that the integrated priority-quality budgeting model significantly contributes to improving school quality by ensuring transparency, effectiveness, and sustainability in educational financing. Recommendations include adopting this model in other Islamic educational institutions and strengthening stakeholder participation in financial oversight. Rendahnya mutu pendidikan di Indonesia sebagian besar disebabkan oleh pengelolaan keuangan yang tidak efektif di lembaga pendidikan, khususnya di tingkat sekolah dasar. Penelitian ini bertujuan menganalisis dan menemukan prinsip, proses, dan strategi pengelolaan pembiayaan pendidikan dalam meningkatkan mutu sekolah. Pendekatan kualitatif dengan rancangan studi kasus multikasus digunakan dalam penelitian ini. Data dikumpulkan melalui wawancara mendalam, observasi peran serta, dan studi dokumentasi. Temuan penelitian menunjukkan tiga komponen utama. Pertama, prinsip manajemen pembiayaan dikembangkan berdasarkan nilai ibadah, biaya ditanggung bersama, kualitas Islam yang berdaya saing, pemenuhan standar nasional dan internasional, serta pengelolaan yang amanah dan jujur. Kedua, proses pengelolaan meliputi perencanaan anggaran terpadu berbasis prioritas, pelaksanaan dengan sistem berbasis tingkat, evaluasi model internal, dan pertanggungjawaban melalui audit keuangan dan kinerja. Ketiga, strategi yang diterapkan adalah penyusunan anggaran melalui RKAS/RKAM, pembukuan oleh bendahara yayasan, dan pemeriksaan oleh pimpinan yayasan serta pemangku kepentingan. Penelitian ini menyimpulkan bahwa model penganggaran terpadu berbasis prioritas mutu berkontribusi signifikan dalam peningkatan mutu sekolah. Rekomendasi diberikan untuk mengadopsi model ini di lembaga pendidikan Islam lainnya.